Strategic antagonism: how Lactobacillus plantarum counters Staphylococcus aureus pathogenicity - Bui, Ly Tuan Kiet; Bushra, Fariha Alam; Rattananon, Pirachat; Rimi, Arifa Afrose; Lee, Carmen; Tahmid, S. M.; Tisha, Sumaiya Akter; Jisan, Irfan Fayaz; Das, Rachita; Sneha, Jahin Ibnat; Pitts, Victoria; Owasanoye, Olalekan Uchechukwu; et al. (Frontiers in Microbiology, 2025)
Staphylococcus aureus is a clinically significant pathogen known for its antibiotic resistance, immune evasion, and biofilm formation, making it a major contributor to persistent infections. Lactobacillus plantarum, a versatile probiotic bacterium, has emerged as a promising antagonist against S. aureus through multifaceted inhibitory mechanisms. This review synthesizes current evidence on the antagonistic interactions between L. plantarum and S. aureus, highlighting bacteriocin-mediated membrane disruption, quorum sensing interference, biofilm degradation, and metabolic competition. In addition, we explore how L. plantarum contributes to a less favorable inflammatory environment for S. aureus by modulating local immune responses at infection sites. Clinical relevance is explored across diverse anatomical sites such as the skin, vaginal tract, urinary system, and gastrointestinal tract, where L. plantarum demonstrates both direct and adjunctive therapeutic potential. We also consider environmental influences like pH and nutrient availability that modulate this antagonism. Together, the findings position L. plantarum as a compelling candidate for probiotic-based interventions against persistent and device-associated S. aureus infections.